Dog‐assisted therapy in the dental clinic: Part A—Hazards and assessment of potential risks to the health and safety of humans - Anne M. Gussgard (Clinical and Experimental Dental Research, 2019)
Abstract Background Dog‐assisted therapy in the dental clinic may be an attractive alternative to sedation for anxious patients. Including a dental therapy dog in a clinical setting introduces new hazards and potential risks to health and safety for both humans and animal. Objectives The study aims to describe potential hazards associated with risks to humans by having a therapy dog present in the dental clinic and to provide guidance on best practices to minimise and control risks for the patients, the dentist, and the dental clinic staff. Materials and Methods Literature searches in Medline, Clinicaltrials.gov, and Google Scholar for qualitative and quantitative assessments of hazards and risks associated with the use of therapy dogs in health care settings, in combination with a review of the reference list of the included studies. Identified hazards and risks were analysed with respect for the health and welfare of humans in a dental clinic setting that involves the presence of a therapy dog. Results Potential risks to health and safety for humans in dental clinics that offer dog‐assisted therapy can be categorised within four general categories of hazards: the dog as a source of zoonotic pathogens and human diseases, exposure to canine allergens, adverse animal behaviour, and dangers associated with high activity in a congested dental clinic operatory. Risks to humans are reduced by maintaining awareness amongst the dental clinic staff and the dog handler of all potential hazards in the dental clinic, and on how to reduce these hazards as well as adverse events that may scare the dental therapy dog. Conclusions Risks to the health and safety of humans in the presence of therapy dog in the clinics are present but are low if the dental clinical staff and dog handlers comply with best practices.